Analytical approach for global load-slip behaviour of FRP plates externally bonded to brittle substrates with anchors. (1st March 2019) - Sturm, A.B.; Visintin, P.; Vaculik, J.; Oehlers, D.J.; Seracino, R.; Smith, S.T.
Abstract: A partial interaction procedure is developed for obtaining analytical solutions for the global load-slip behaviour of fibre-reinforced polymer plates adhesively bonded and mechanically anchored to brittle substrates. This is performed by adopting a matrix approach where the slip and slip strain at any point is given by the product of a solution matrix which is a function of: the position; the zone of solution - whether it is elastic, softening or debonding; and a coefficient vector. It is shown that the procedure can be used as a convenient research tool for extracting the material bond properties from standard experimental pull-push tests, or for use in advanced numerical simulations to develop anchorage systems for structures retrofitted with fibre-reinforced polymer (FRP) composites.